RETRACTED: New prospects in bowel preparation for examination - R. G. Myazin (Амбулаторная хирургия, 2017)
RETRACTED ARTICLEQualitatively new techniques in the preparation of the colon for endo-scopic, radiological, ultrasonic methods of investigation, as well as surgical interventions, allow for a more reliable visualization of all parts of the intestine. These techniques help to carry out a more productive investigation of the large intestine, while the new, gentle preparation is better tolerated by patients. One of the novel medications for bowel preparation is Phospho-soda which is easy to use and has a high safety profile.